CAFs shape myeloid‐derived suppressor cells to promote stemness of intrahepatic cholangiocarcinoma through 5‐lipoxygenase. Issue 1 (5th December 2021) - Lin, Yuli; Cai, Qian; Chen, Yu; Shi, Tiancong; Liu, Weiren; Mao, Li; Deng, Bo; Ying, Zhen; Gao, Yuan; Luo, Haoyang; Yang, Xuguang; Huang, Xiaowu; et al.
Abstract: Background and Aims: We previously demonstrated that cancer‐associated fibroblasts (CAFs) promote tumor growth through recruitment of myeloid‐derived suppressor cells (MDSCs). 5‐lipoxygenase (5‐LO) is highly expressed in myeloid cells and is critical for synthesizing leukotriene B4 (LTB4), which is involved in tumor progression by activating its receptor leukotriene B4 receptor type 2 (BLT2). In this study, we investigated whether and how CAFs regulate MDSC function to enhance cancer stemness, the driving force of the cancer aggressiveness and chemotherapy refractoriness, in highly desmoplastic intrahepatic cholangiocarcinoma (ICC). Approach and Results: RNA‐sequencing analysis revealed enriched metabolic pathways but decreased inflammatory pathways in cancer MDSCs compared with blood MDSCs from patients with ICC. Co‐injection of ICC patient‐derived CAFs promoted cancer stemness in an orthotopic ICC model, which was blunted by MDSC depletion. Conditioned media (CM) from CAF‐educated MDSCs drastically promoted tumorsphere formation efficiency and stemness marker gene expression in ICC cells. CAF‐CM stimulation increased expression and activity of 5‐LO in MDSCs, while 5‐LO inhibitor impaired the stemness‐enhancing capacity of MDSCs in vitro and in vivo. Furthermore, IL‐6 and IL‐33 primarily expressed by CAFs mediated hyperactivated 5‐LO metabolism in MDSCs. We identified the LTB4‐BLT2 axis as the critical downstream metabolite signaling of 5‐LO in promoting cancer stemness, as treatment with LTB4 was elevated in CAF‐educated MDSCs, or blockade of BLT2 (which was preferentially expressed in stem‐like ICC cells) significantly reduced stemness‐enhancing effects of CAF‐educated MDSCs. Finally, BLT2 blockade augmented chemotherapeutic efficacy in ICC patient‐derived xenograft models. Conclusions: Our study reveals a role for CAFs in orchestrating the optimal cancer stemness‐enhancing microenvironment by educating MDSCs, and suggests the 5‐LO/LTB4‐BLT2 axis as promising therapeutic targets for ICC chemoresistance by targeting cancer stemness.